Selective Leaching Bastnaesite from Bayan Obo Rare Earth Concentrate and the Recovery Process of Rare Earths, Aluminum, Fluoride and Calcium - Yanzhu Liu; Huifang Xiao; Lihui Liu; Xiaofan Ye; Xiaoqian Hu; Yanrong Ding; Yongxiu Li (Metals)
Bayan Obo rare earth concentrate (BOREC) is composed of bastnaesite, monazite and fluorite, which is recognized as a refractory mineral in the world. In order to solve the problems of waste gas treatment and comprehensive utilization efficiency of BOREC decomposed by the current concentrated sulfuric acid roasting method (500–700 °C), H2SO4-HCl mixed acid assisted by aluminum salt was used to leach out the bastnaesite, and the optimal conditions were determined as follows: c(H+) = 7 mol/L, c(1/2H2SO4):c(HCl) = 5:1, c(Al2(SO4)3) = 0.25 mol/L, temperature 135 °C, liquid–solid ratio of 42:1, and reaction time 3 h. At this time, the leaching rates of concentrate and rare earth (La, Ce, Pr and Nd) were 74.08% and 71.95%, respectively, and the decomposition rate of bastnaesite was 96.83%. At the same time, the yield of calcium sulfate was 77.35% and the purity was 99.22%. Subsequently, sodium sulfate was added with m(Na2SO4):m(RE2O3) = 2.5:1, and the recovery rate of rare earth was 99.5%, and the purity of rare earth double salt product was 98.47% at a temperature of 90 °C. After most of the acid had been extracted with triethyloctanamine, sodium fluoride was added with a fluorine–aluminum ratio of 6:1, sodium carbonate was used to adjust pH = 3, and cryolite was obtained with a purity of 95.59% and an aluminum recovery rate of 99.6% at 90 °C. Since the separation of bastnaesite and monazite has been basically realized in the leaching stage, it is conducive to the docking of subsequent alkali decomposition and recovery of trisodium phosphate, realizing the comprehensive recovery of rare earth, fluorine, calcium, aluminum and phosphorus.